Verse written in Devanagri script - Temples of India Project Team (Jio Institute, 2024)
A verse is written in Devanagari script above the lalatbimba (lintel) of garbhagriha (sanctum sanctorum) entrance to the Parshvanath shrine, in the Adinatha Temple.